Click‐Chemistry (CuAAC) Trimerization of an αvβ6 Integrin Targeting Ga‐68‐Peptide: Enhanced Contrast for in‐Vivo PET Imaging of Human Lung Adenocarcinoma Xenografts. (9th June 2020) - Quigley, Neil Gerard; Tomassi, Stefano; di Leva, Francesco Saverio; Di Maro, Salvatore; Richter, Frauke; Steiger, Katja; Kossatz, Susanne; Marinelli, Luciana; Notni, Johannes
Abstract: αv β6 Integrin is an epithelial transmembrane protein that recognizes latency‐associated peptide (LAP) and primarily activates transforming growth factor beta (TGF‐β). It is overexpressed in carcinomas (most notably, pancreatic) and other conditions associated with αv β6 integrin‐dependent TGF‐β dysregulation, such as fibrosis. We have designed a trimeric Ga‐68‐labeled TRAP conjugate of the αv β6 ‐specific cyclic pentapeptide SDM17 (cyclo[RGD‐Chg‐E]‐CONH2 ) to enhance αv β6 integrin affinity as well as target‐specific in‐vivo uptake. Ga‐68‐TRAP(SDM17)3 showed a 28‐fold higher αv β6 affinity than the corresponding monomer Ga‐68‐NOTA‐SDM17 (IC50 of 0.26 vs. 7.4 nM, respectively), a 13‐fold higher IC50 ‐based selectivity over the related integrin αv β8 (factors of 662 vs. 49), and a threefold higher tumor uptake (2.1 vs. 0.66 %ID/g) in biodistribution experiments with H2009 tumor‐bearing SCID mice. The remarkably high tumor/organ ratios (tumor‐to‐blood 11.2; ‐to‐liver 8.7; ‐to‐pancreas 29.7) enabled high‐contrast tumor delineation in PET images. We conclude that Ga‐68‐TRAP(SDM17)3 holds promise for improved clinical PET diagnostics of carcinomas and fibrosis. Abstract : See three with glee : Tethering three rather than a single peptidic αv β6 integrin ligand to a radionuclide lets tumor tissue light up brightly in tomographic images, potentially enabling a more sensitive diagnosis of various cancers.